2016
DOI: 10.1021/acs.langmuir.6b02375
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Monometallic (Au and Pd) and Bimetallic (AuPd) Nanoparticles Using Carbon Nitride (C3N4) Quantum Dots via the Photochemical Route for Nitrophenol Reduction

Abstract: In this study, we report the synthesis of monometallic (Au and Pd) and bimetallic (AuPd) nanoparticles (NPs) using graphitic carbon nitride (g-CN) quantum dots (QDs) and photochemical routes. Eliminating the necessity of any extra stabilizer or reducing agent, the photochemical reactions have been carried out using a UV light source of 365 nm where CN QD itself functions as a suitable stabilizer as well as a reducing agent. The g-CN QDs are excited upon irradiation with UV light and produce photogenerated elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 111 publications
(51 citation statements)
references
References 54 publications
3
47
0
1
Order By: Relevance
“…Figure a,b shows UV–vis spectra of the reaction mixture (containing 5 mg CDs@Ag 3 PO 4 ) at different time intervals and the same temperature (0 °C) without and with visible irradiation, respectively. By contrast, the maximum absorbance peak at 400 nm, which is assigned to the characteristic absorbance peak of 4‐NP, decreases much slowly without visible irradiation as well as no obvious absorbance peak at 297 nm. Under the visible light, however, the absorbance peak at 400 nm gradually decreases as the visible irradiation time proceeds, simultaneously accompanied by the increase in intensity of the 297 nm peak attributed to 4‐AP .…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…Figure a,b shows UV–vis spectra of the reaction mixture (containing 5 mg CDs@Ag 3 PO 4 ) at different time intervals and the same temperature (0 °C) without and with visible irradiation, respectively. By contrast, the maximum absorbance peak at 400 nm, which is assigned to the characteristic absorbance peak of 4‐NP, decreases much slowly without visible irradiation as well as no obvious absorbance peak at 297 nm. Under the visible light, however, the absorbance peak at 400 nm gradually decreases as the visible irradiation time proceeds, simultaneously accompanied by the increase in intensity of the 297 nm peak attributed to 4‐AP .…”
Section: Resultsmentioning
confidence: 93%
“…By contrast, the maximum absorbance peak at 400 nm, which is assigned to the characteristic absorbance peak of 4‐NP, decreases much slowly without visible irradiation as well as no obvious absorbance peak at 297 nm. Under the visible light, however, the absorbance peak at 400 nm gradually decreases as the visible irradiation time proceeds, simultaneously accompanied by the increase in intensity of the 297 nm peak attributed to 4‐AP . As a result, almost complete conversion of 4‐NP to 4‐AP was achieved within 20 min irradiation.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Moreover, in comparison to the numerous investigation interests on other photocatalytic reactions by g‐CN or g‐CN based composites, fewer studies have been reported on photo‐reduction of PNP. And, in most cases g‐CN was only used as photo‐reduction medium or supporter to prepare or load noble metal catalysts …”
Section: Introductionmentioning
confidence: 99%